Penataan legatitas usaha bagi UMKM “Minthul Cryspi” di Desa Karangtengah Kecamatan Tuntang - Fauzi, Adnan Ali; Hidayat, Rina Andriani; Arifah, Indirotul Nur; Khasanah, Uswatun; Hakim, Muhammad Khusnul; Winandari, Fadya (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
Karangtengah Village, Semarang Regency has a lot of potential for Micro, Small and Medium Enterprises (MSMEs) which continue to develop. However, for the majority of MSME actors in Karangtengah Village there is no arrangement and no business legality from the government, some business actors even do not know about business legality. In fact, with the existence of MSMEs, business actors are required to have permits for the business activities they carry out, and in this case, the permit required is a Business Identification Number (NIB). One of the MSMEs in Karangtengah Village is the "Minthul Crispy" MSME. Even though this business has been operating, it has not yet obtained a business permit for the activities being carried out. The aim of this research is to support MSMEs to obtain business legality. The method used in research is to provide community service activities in the form of assistance for the NIB registration process. The NIB registration process can be done online via the Online Single Submission (OSS) platform. This community service activity will take place from February 18 2024 to February 26 2024. The result of this activity is that MSMEs will be helped more in developing their business.